PERUBAHAN TATAKELOLA TAMAN NASIONAL: STUDI KASUS DI TAMAN NASIONAL GUNUNG HALIMUN SALAK - Bambang Supriyanto; Hideyuki Kubo; Atih Sundawiati (Media Konservasi, 2010)
Changes in national parks (NP) governance include 1) change in NP management policy which was originally precedence for protection and preservation, now includes real economy for the community, 2) implementation process of the change at field level. This paper discusses the governance change in Gunung Halimun Salak National Park (TNGHS) and its impacts on resource users. Change in governance could take place if the interactive process that occurred between the Head of the National Park, field officers and the community included: (1) Clear and simple policy guidance from the Head of NP on the policy implementation of the new governance be given to field officers, (2) develop relationship between field officers and local community through active interaction. Shift in the implementation technique of NP governance for protection and preservation from "restrictions and provision of sanctions" to "participatory conservation" to achieve the goal of NP resources utilization for the community. The analysis showed that change in NP governance was achieved through the approach of participatory conservation processes, learning and increasing confidence that comes naturally among the field officers and local communities and conservation practices by local communities. Keywords: change in NP governance, restrictions and provisions of sanctions, participatory conservation, learning, increasing confidence